2022
DOI: 10.48550/arxiv.2202.03521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High D/H ratios in water and alkanes in comet 67P/Churyumov-Gerasimenko measured with the Rosetta/ROSINA DFMS

Daniel R. Müller,
Kathrin Altwegg,
Jean-Jacques Berthelier
et al.

Abstract: Context. Isotopic abundances in comets are key to understanding and reconstructing the history and origin of material in the Solar System. Data for deuterium-to-hydrogen (D/H) ratios in water are available for several comets. However, no long-term studies of the D/H ratio in water of a comet during its passage around the Sun have been reported. Linear alkanes are important organic molecules, which have been found on several Solar System bodies, including comets. To date, their deuteration is still poorly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Henning and Salama, 1998) to places in our solar system. Examples are the C 2 H 4 haze on Triton (Ohno et al, 2021) or various different molecules on comets such as 67P (Müller et al, 2022). Huang et al (2021) found that the detection of NH 3 can be a biosignature on planets, where a deep atmosphere is excluded.…”
Section: Implications For Atmospheric Biosignaturesmentioning
confidence: 99%
“…Henning and Salama, 1998) to places in our solar system. Examples are the C 2 H 4 haze on Triton (Ohno et al, 2021) or various different molecules on comets such as 67P (Müller et al, 2022). Huang et al (2021) found that the detection of NH 3 can be a biosignature on planets, where a deep atmosphere is excluded.…”
Section: Implications For Atmospheric Biosignaturesmentioning
confidence: 99%